PEMBELAJARAN PAI PADA SISWA TUNAGRAHITA (Studi Kasus Di SMALB Negeri Tenggarong) - Akhmad Riadi (Fakultas Agama Islam Universitas Kutai Kartanegara, 2018)
This study aims to determine the learning of Islamic Education in mentally disabled students in Tenggarong State Public High School, related to Learning Strategies, Models, Methods and Learning Media. The research method uses a qualitative description method, where the data collection uses observation, interviews and documentation. Data is then analyzed through data reduction stages, data models, and conclusions. The results of this study are the learning of Islamic Education in Tenggarong State SLB in high school level in students with mental retardation in accordance with learning in general. The strategies used by Islamic religious education teachers in learning also apply strategies in general, while the learning methods used are lecture method, description (movement) and practice. To support the PAI learning strategy effectively the teacher uses visual and audio-visual media in the form of pictures / posters, movements and videos on the practice of ablution and prayer. Then to strengthen the use of media the learning model is made in a fun way that is the teacher is directly involved and active during the learning process.